Global Business Strategy Multinational Corporations Venturing into Emerging Markets - Motohashi, Kazuyuki (Springer Texts in Business and Economics, 2015)
Emerging Markets/Globalization; Innovation/Technology Management; Business Strategy/Leadership; International Economics; Operations Management